2020
DOI: 10.1111/tbed.13768
|View full text |Cite
|
Sign up to set email alerts
|

Improving laboratory diagnostic capacities of emerging diseases using knowledge mapping

Abstract: is currently employed GlaxoSmithKline Vaccines. The positions and opinions presented in this article reflect the work carried out during her employment at Sciensano at the time of the study conduct and are not intended to represent the views or scientific works of GlaxoSmithKline. # Yves Van der Stede is currently employed with the European Food Safety Authority (EFSA) in the ALPHA Unit that provides scientific and administrative support to EFSA's scientific activities in the area of Animal Health and Welfare.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Stirling and Scoones (2009) noted that governance of infectious disease risks (e.g., requires an understanding of often indeterminate interactions between diverse, complex, open, and dynamic human and natural systems. Furthermore, the findings of Cargnel et al (2021) revealed the usefulness of knowledge mapping as a tool for visualising and identifying gaps and ultimately gaining insight into alternatives for better preparedness and responsiveness in different epidemiological scenarios. Therefore, mapping and sharing knowledge on public health emergencies, such as COVID-19, could allow key knowledge to be rapidly identified and could connect various users and stakeholders at various levels, e.g., national, regional and international levels.…”
Section: Knowledge Mappingmentioning
confidence: 99%
“…Stirling and Scoones (2009) noted that governance of infectious disease risks (e.g., requires an understanding of often indeterminate interactions between diverse, complex, open, and dynamic human and natural systems. Furthermore, the findings of Cargnel et al (2021) revealed the usefulness of knowledge mapping as a tool for visualising and identifying gaps and ultimately gaining insight into alternatives for better preparedness and responsiveness in different epidemiological scenarios. Therefore, mapping and sharing knowledge on public health emergencies, such as COVID-19, could allow key knowledge to be rapidly identified and could connect various users and stakeholders at various levels, e.g., national, regional and international levels.…”
Section: Knowledge Mappingmentioning
confidence: 99%
“…Cargnel et al improved the laboratory diagnostic research capacity of emerging diseases using knowledge mapping. Raju Vaishya has examined the trend of publishing in 3D printing in the eld of orthopedics using KMD (Cargnel et al 2020). Zhao conducted research to reveal the general state of research on the Ebola virus by mapping knowledge of the Ebola virus literature around the world (Zhao et al 2015).…”
Section: Mapping Knowledge Domainmentioning
confidence: 99%